Pathogenesis of murine enterovirus myocarditis: virus dissemination and immune cell targets. - Klingel, K (1996)
In order to identify organ and cellular targets of persistent enterovirus infection in vivo, immunocompetent mice (SWR/J, H-2q) were inoculated intraperitoneally with coxsackievirus B3 (CVB3). By use of in situ hybridization for the detection of enteroviral RNA, we show that CVB3 is capable of inducing a multiorgan disease. During acute infection, viral RNA was visualized at high levels in the heart muscle, pancreas, spleen, and lymph nodes and at comparably low levels in the central nervous system, thymus, lung, and liver. At later stages of the disease, the presence of enteroviral RNA was found to be restricted to the myocardium, spleen, and lymph nodes. To characterize infected lymphoid cells during the course of the disease, enteroviral RNA and cell-specific surface antigens were visualized simultaneously in situ in spleen tissue sections. In acute infection, the majority of infected spleen cells, which are located primarily at the periphery of lymph follicles, were found to express the CD45R/B220+ phenotype of pre-B and B cells. Whereas viral RNA was also detected in certain CD4+ helper T cells and Mac-1+ macrophages, no enteroviral genomes were identified in CD8+ cytotoxic/suppressor T cells. Later in disease, the localization of enteroviral RNA revealed a persistent type of infection of B cells within the germinal centers of secondary follicles. In addition, detection of the replicative viral minus-strand RNA intermediate provided evidence for virus replication in lymphoid cells of the spleen during the course of the disease. These data indicate that immune cells are important targets of CVB3 infection, providing a noncardiac reservoir for viral RNA during acute and persistent myocardial enterovirus infection.